AI Adoption in Business: Opportunities and Challenges for Start-ups - Dede Irman; Deva Putra (International Journal of Business, Economics, and Social Development, 2025)
Artificial intelligence (AI) has become a technology that plays an important role in business transformation, including in the start-up sector. This study aims to analyze the opportunities and challenges in adopting AI in start-up businesses and its impact on company performance. The research method used is a qualitative and quantitative approach by collecting data through surveys, interviews, and literature studies. The results of the study show that AI provides various benefits for start-ups, such as increasing operational efficiency, optimizing decision-making, personalizing customer service, and reducing labor costs. The fintech and e-commerce sectors are the industries with the highest rates of AI adoption due to the need for automation and data security. However, the implementation of AI also faces various challenges, including high costs, limited expertise, integration with legacy systems, and data security and regulatory issues. Further analysis shows that start-ups that successfully adopt AI have a mature strategy in technology investment and human resource development. In addition, the effective implementation of AI can increase the competitiveness of start-ups and support sustainable business growth. Therefore, a strategic approach is needed in facing the challenges of AI implementation so that the benefits obtained can be optimized. This study is expected to provide insights for business owners, investors, and policy makers in developing more effective AI adoption strategies in the future.